Structure of the gene coding for the sequence-specific DNA-methyltransferase of the B. subtilis phage SPR. - Pósfai, G (1984)
The nucleotide sequence of the gene coding for the 5'-GGCC and 5'-CCGG specific DNA methyltransferase of the Bacillus subtilis phage SPR was determined by the Maxam-Gilbert procedure. Transcriptional and translational signals of the sequence were assigned with the help of S1 mapping and translation in E. coli minicells. The gene codes for a 49 kd polypeptide. The amino acid sequence of the SPR methylase shows regions of homology with the sequence of the 5'-GGCC-specific BspRI modification methylase.